Productivity and nutritional value of common beans with organic fertilization in Durango, Mexico - Ortiz-Sánchez, Ixchel; Gamero-Posada, Erika; Nava-Berumen, Cynthia; Valdez-Ortega, Sonia; Alaniz-Villanueva, Oscar (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
Biofertilizers help to increase crop yields and nutritional quality, reducing the use of agrochemicals that affect ecosystems and human health. The objective of this study was to evaluate the yield and nutritional value of the Pinto Rarámuri variety bean, under an organic fertilization scheme in rainfed conditions in Durango, Mexico. Sowing was carried out in open fields in Villa Montemorelos, Durango, using a randomized complete block design with six treatments [manure tea (tea), sewage sludge (sludge), super lean (lean), commercial organic fertilizer (foc), chemical fertilizer (fqf) and control] five repetitions, 30 plots and five plants per plot as experimental unit. The variables were: emergence percentage, height and pods per plant, seeds per pod, seed thickness and length, weight of 100 seeds, yield, crude fiber percentage, protein, ash, fat, and nitrogen-free extract. A two-way analysis of variance and Tukey’s comparison of means (p ≤ 0.05) were performed. The treatments showed statistical difference, the highest yield and weight of 100 seeds was presented by sludge, fqf and foc; while the highest number of pods and plant height was obtained by sludge and fqf. The lowest yield, pods per plant, seeds per pod and plant height were observed in control. The nutritional value presented statistical equality between treatments. The use of organic fertilization is a sustainable alternative to increase bean productivity in the state of Durango, without disturbing its nutritional quality.